Metode Sintesis Nanopartikel-TiO2 : A Review - Karlina, Lilis; Sanjaya, Hary; Budiman, Septian (MASALIQ, 2023)
Titanium dioxide is an important type of material that has been widely researched by experts. TiO2 can be used as a catalyst and in various other applications because it has unique electronic and optical properties. TiO2 compounds have been synthesized using various synthesis methods. The aim of this review is to summarize various types of TiO2 synthesis methods, morphology and crystallization of nanostructured TiO2. The research method used is literature study or literature study. The results of the reviews show that TiO2 can be synthesized by various methods, namely hydrothermal, solvothermal, sol-gel, direct oxidation, chemical vapor deposition, electrodeposition, sonochemistry and microwaves. The crystal structure phase that is often found is the anatase phase.